Patient Navigation Overcoming Barriers to Care (Springer New York, 2018)
Documenting the success and result of patient navigation programs, this book represents the culmination of years of research and practical experience by scientific leaders in the field. A practical guide to creating, implementing, and evaluating successful programs, Patient Naviation - Overcoming Barriers to Care offers a step-by-step guide towards creating and implementing a patient navigation program within a healthcare system. Providing a formal structure for evaluation and quality improvement this book is an essential resource for facilities seeking patient navigation services accreditation.